Educação Física e promoção da saúde : uma revisão de perspectivas teórico-metodológicas no Brasil - Heredia y Antunes, Diogo Silveira; Knuth, Alan Goularte; Damico, Jose Geraldo (2020)
In the complexity of the performance of Physical Education in health promotion, it is possible to identify different epistemological perspectives in the know-how of workers. The aim of this article, of an essay character, is to point out these perspectives, seeking to perceive its theoretical and historical influences, as well as the paths it has been going through in publications, authors that stand out and focuses of interest. Through non-systematic searches in databases and journals, publications and legal frameworks linking Physical Education and health promotion were studied. The existence of four theoretical-methodological perspectives was found: epidemiological, which points out the positive relation between physical activity and the lower incidence of diseases; post structuralist, which links to the production of subjectivity and social relations in the promotion of health; historical-dialectical materialism, which reflects on the social interrelationships and the means of production and exploitation; and the integrative perspective, which links to a vitalist perspective, where health comes to be perceived as the pursuit of the wholeness of being. It is important to emphasize that the presentation of these perspectives in a linear way is a didactic resource, but that in the reality of the professional practice they do not always show themselves with boundaries clearly defined, being able to present themselves in a hybrid and interrelated way.
Na complexidade da atuação da educação física na promoção da saúde é possível identificar diferentes perspectivas epistemológicas no saber-fazer dos trabalhadores. A intenção deste artigo, de caráter ensaístico, é apontar estas perspectivas, buscando perceber suas influencias teóricas e históricas, assim como os caminhos que vem percorrendo em publicações, autores que se destacam e focos de interesse. Por meio de buscas não sistemáticas em bancos de dados e periódicos, foram encontradas publicações e marcos legais que ligam educação física e promoção da saúde. Conclui-se a existência de quatro perspectivas teórico-metodológicas: epidemiológica, aponta a relação positiva entre a atividade física e a menor incidência de doenças; pós estruturalista ligada a produção de subjetividade e relações sociais, na promoção da saúde; materialismo histórico-dialético reflete a respeito das inter-relações sociais e dos meios de produção e exploração; e a perspectiva integrativa ligada a uma perspectiva vitalista, onde a saúde passa a ser percebida como a busca da inteireza do ser. É importante ressaltar que a apresentação destas perspectivas de forma linear é um recurso didático, mas que na realidade da prática profissional nem sempre mostram-se com fronteiras claramente delineadas, podendo se apresentar de forma hibrida e inter-relacionada.
Keywords: Health promotion; Theoretical-methodological perspectives; Physical education; Promoção da saúde^lpt; Perspectivas teórico-metodológicas; Educação física